(untitled) (Journal of Information and Communication Technology, 2014)
Business Intelligence (BI), which is the process of collecting, analysing, and transforming data using Data Warehouse (DW) is seen as one of the growing approaches to provide meaningful information for the Malaysian Ministry of Higher Education (MOHE). MOHE is responsible for managing various activities to encourage graduate entrepreneurs to venture into businesses and ensure that the country has many successful entrepreneurs. Therefore, systematic and accurate information needs to be available for planning, implementing, and monitoring entrepreneurs’ performances. This paper proposes the modelling and designing of the graduate entrepreneur profi le system – Intelligent Profi le Analysis Graduate Entrepreneur (iPAGE) using the BI approach. Two main methodologies were used, namely the Requirements Centric Operational Data Store (ReCODS) and the Rapid Application Development (RAD) to model and design this system. The iPAGE was validated and evaluated by users, entrepreneurs’ personnel and DW experts. Indeed, the approach will be used to benchmark the development of an entrepreneurial information system in the future.